Using HTML 4 - Java 1.1 - Javascript 1.2 : - Ladd, Eric (Que, 1998)
A complete tutorial and reference guide teaches a vast array of new Web programming skills on advanced-level topics that Webmasters need the most, such as building Web databases, interactive forms, and Webcasting.